2021
DOI: 10.1038/s41391-020-00317-w
|View full text |Cite
|
Sign up to set email alerts
|

Body composition, physical function and quality of life in healthy men and across different stages of prostate cancer

Abstract: BACKGROUND: Androgen deprivation therapy (ADT) for prostate cancer (PC) has detrimental effects on physical function and quality of life (QoL), but the addition of androgen receptor signaling inhibitors (ARSI) on these outcomes is unclear. PURPOSE: To compare body composition, physical function, and QoL across progressive stages of PC and non-cancer controls (CON). METHODS: In men with hormone sensitive PC (HSPC, n=43) or metastatic castratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Fischer et al uncovered that skeletal muscle area of mCRPC patients exhibited a significant reduction after abiraterone or enzalutamide treatment 34 . Hanson et al demonstrated that percent lean of mCRPC was lower than HSPC 35 . However, up to date, there were no studies focusing on exploring whether body composition profiles before AA treatment could predict biochemical response to AA and prognosis in patients with mCRPC with prior chemohormonal therapy at hormone‐sensitive stage.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al uncovered that skeletal muscle area of mCRPC patients exhibited a significant reduction after abiraterone or enzalutamide treatment 34 . Hanson et al demonstrated that percent lean of mCRPC was lower than HSPC 35 . However, up to date, there were no studies focusing on exploring whether body composition profiles before AA treatment could predict biochemical response to AA and prognosis in patients with mCRPC with prior chemohormonal therapy at hormone‐sensitive stage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, men with mCRPC who were started on ARPis, as opposed to mCSPC patients on ADT alone, were noted to have the lowest functional performance in tasks against gravity, such as the timed up and go and stair climbing. 35 Hanson et al also noted that ADT duration was similar between mCSPC and mCRPC groups, which suggests that the addition of an ARPis contributes, in part, to further worsening of body composition and decline in physical function. Even so, changes in physical performance with ARPis like enzalutamide are not always negative and do not only impact tests against gravity.…”
Section: Geriatric Assessment and Arpismentioning
confidence: 93%
“…Objective changes in physical function and body composition occur as the prostate cancer stage advances. 35 These changes may be key to understanding enzalutamide’s objective and physical consequences.…”
Section: Geriatric Assessment and Arpismentioning
confidence: 99%
See 2 more Smart Citations